Identification of biomarkers and genetic approaches toward chronic obstructive pulmonary disease. Issue 10 (25th March 2019) - Wadhwa, Ridhima; Aggarwal, Taru; Malyla, Vamshikrishna; Kumar, Nitesh; Gupta, Gaurav; Chellappan, Dinesh Kumar; Dureja, Harish; Mehta, Meenu; Satija, Saurabh; Gulati, Monica; Maurya, Pawan Kumar; Collet, Trudi; et al.
Abstract: Chronic obstructive pulmonary disease accounts as the leading cause of mortality worldwide prominently affected by genetic and environmental factors. The disease is characterized by persistent coughing, breathlessness airways inflammation followed by a decrease in forced expiratory volume1 and exacerbations, which affect the quality of life. Determination of genetic, epigenetic, and oxidant biomarkers to evaluate the progression of disease has proved complicated and challenging. Approaches including exome sequencing, genome‐wide association studies, linkage studies, and inheritance and segregation studies played a crucial role in the identification of genes, their pathways and variation in genes. This review highlights multiple approaches for biomarker and gene identification, which can be used for differential diagnosis along with the genome editing tools to study genes associated with the development of disease and models their function. Further, we have discussed the approaches to rectify the abnormal gene functioning of respiratory tissues and various novel gene editing techniques like Zinc finger nucleases (ZFN), transcription activator‐like effector nucleases (TALEN), and clustered regulatory interspaced short palindromic repeats/CRISPR‐associated protein 9 (CRISPR/Cas9). Abstract : This review highlights multiple approaches for biomarker and gene identification which can be used for differential diagnosis along with the genome editing tools to study genes associated with the development of disease and models their function. Further, we have discussed the approaches to rectify the abnormal gene functioning of respiratory tissues and various novel gene editing techniques like Zinc finger nucleases (ZFN), transcription activator‐like effector nucleases (TALEN) and clustered regulatory interspaced short palindromic repeats/CRISPR‐associated protein 9 (CRISPR/Cas9)